Analisis Makna Teks Fabel Karya Jean de La Fontaine “la Cigale et la Fourm, le Coq et le Renard, le Lion devenu vieux” - Dede Kharisma Dewi (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Fables are literary works in the form of literary texts in the form of exposure to stories and poems with animal characters. This study aims to determine the meaning and meaning of the Fable text of Jean de la Fontaine's three literary works,